Treatment of chronic graft-versus-host disease with bortezomib - Pai, Chien-Chun Steven (American Society of Hematology, 2014)
Chronic graft-versus-host disease (cGVHD) following allogeneic hematopoietic stem cell transplantation (HSCT) has emerged as a predominant complication following HSCT and has a distinct etiology. We and others have previously demonstrated that bortezomib, a proteasome inhibitor, can prevent but not treat acute GVHD in mice. To assess the effects of bortezomib on cGVHD, a mouse minor histocompatibility antigen-mismatched strain combination was used to mimic clinical cGVHD sclerodermatous pathogenesis and phenotype. Treatment of ongoing cGVHD with bortezomib ameliorated cutaneous lesions, which were also associated with a reduction in total numbers of germinal center B cells and lower B-cell activating factor gene expression levels in cutaneous tissues. Importantly, lymphoma-bearing mice receiving allogeneic HSCT with bortezomib preserved graft-versus-tumor (GVT) effects. Based on these animal studies, we initiated an intrapatient dose escalation clinical trial in patients with extensive steroid–intolerant, dependent, or resistant cGVHD. Marked clinical improvement was observed in patients, which was also associated with reductions of peripheral B cells and minimal toxicity. These results indicate that bortezomib can be of significant use in the treatment of cGVHD and may also allow for maintenance of GVT. This trial was registered at www.clinicaltrials.gov as #NCT01672229.